Nidoviruses in Aquatic Organisms - Paradigm of a Nascent Concern - Monalisha Kumar; R. Bharathi Rathinam; Gayatri Tripathi (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
The extraordinarily genetically complex Nidovirus is an enveloped, single-stranded RNA virus. This diversified group of viruses has a higher degree of RNA recombination due to its large nested arrangements of sub-genomic mRNA. This is considered to be crucial for accelerating the evolutionary process and pathogenesis of the virus resulting in enhancing their adaptation to rapidly changing environment as well as upgrading them to infect a broad range of host. In general, Nidoviruses are an alarming group of pathogens of terrestrial animals but they have, of late, started affecting a wide range of aquatic animals such as fish and shellfish since the last 20 years. The common Nidoviruses reported from aquatic animals are Bafinivirus i.e. White bream virus, Fathead minnow virus, Chinook salmon bafinivirus from fish; Yellow head virus, Gill-associated virus from shrimp; Eriocheir sinensis ronivirus from crab; Harbour seal coronavirus, Beluga whale coronavirus, Bottlenose dolphin coronavirus from marine mammals. The clinical symptoms associated with this virus infection are mainly noticed in the skin, eye, anterior kidney, spleen and liver whereas gill, lymphoid organ, haemopoietic tissue, midgut, cuticular epithelium, heart, haemocytes in shrimps and ecdysal gland in crabs are the primary target organs of Nidoviruses. It has gained considerable importance in the research area of aquatic animal health with the discovery of first fish Nidovirus in cyprinids but the prevalence, host range, route of infection, mode of transmission and diagnosis of the virus are required to be explored in detail to evaluate the significant risk of Nidoviruses and to control the future outbreak of diseases in aquatic animals.